Effect of rice straw and garbage enzyme addition on soil properties and plant growth of rice - Nguyen-Sy, Toan; Do, Hanh Hong; Tran, Yen Anh Thi; Kieu, Hoa Thi; Huynh Thi Diem, Uyen; Tran, Ngoc-Son (Universitas Sebelas Maret, 2023)
The objective of the current study was to examine the impacts of rice straw and garbage enzyme generated from local vegetable and fruit waste on plant growth and carbohydrate or ammonium extraction from paddy soil after one month of growth in a pot experiment. Samples of topsoil were obtained from a depth of 0-15 cm, and the following treatments were applied: control (10 g soil), RS (adding 30 g soil + 0.6 g rice straw), GE (30 g soil + garbage enzyme), and combination (adding 30 g soil+ rice straw and garbage enzyme) maintained at room temperature. The study findings indicated that there were no observable impacts of rice straw and garbage enzyme application on biomass. However, RS addition seems to reduce root length but enhance shoot length. Soil carbohydrates that were extracted ranged from 61 to 207 mg kg−1 soil, and treatments with rice straw addition exhibited significantly higher levels compared to those without it (p < 0.05). The ammonium content was low. It could be concluded that at the initial seedling stage, rice straw has more effects on soil properties and plant growth than garbage enzyme. To fully assess the effects of rice straw and garbage enzyme on soil properties and plant growth, it is recommended that further research be conducted over longer periods